Muslim clothing online purchases in Indonesia during COVID-19 crisis - Muhartini Salim; Ronal Aprianto; Syaiful Anwar Abu Bakar; Muhammad Rusdi (Economies, 2022)
Today, online Muslim clothing providers in Indonesia are faced with increasing competition in business openness. This condition requires online Muslim clothing providers to be more creative, innovative, effective and efficient by offering Muslim clothing products that are more valuable than competitors'. Therefore, a sophisticated and smart technology planning concept is needed for Muslim fashion consumers and to continue to achieve the benefits obtained by online Muslim clothing providers. This study aims to determine: (1) the influence of attitudes on the online buying intention of Muslim clothing in Indonesia during the COVID-19 crisis (2) the influence of subjective norm on the online buying intention of Muslim clothing in Indonesia during the COVID-19 crisis (3) the influence of perceived behavioral control on the online buying intention of Muslim clothing in Indonesia during the COVID-19 crisis (4) the effect of attitudes on the online buying intention of Muslim clothing in Indonesia during the COVID-19 crisis moderated by religious belief, (5) the effect of subjective norm on the online buying intention of Muslim clothing in Indonesia during the COVID-19 crisis moderated by religious belief, and (6) the effect of perceived behavioral control on the online buying intention of Muslim clothing in Indonesia during the COVID-19 crisis moderated by religious belief. This study uses 1. independent variables, namely: attitudes, subjective norms, and perceived behavioral control. 2. The dependent variable is: Purchase intention. 3. The moderating variable is: religion. The data in this study are obtained from questionnaires distributed to 762 respondents. The method used is purposive sampling to all respondents who shopped online. The method is through the LISREL 8.7 program and t-test. These results indicate that the variables of attitude, subjective norm and perceived behavioral control influence the online buying intention of Muslim clothing in Indonesia during the COVID-19 crisis. They also find that the religious belief variable can moderate the variable of attitude towards the online buying intention of Muslim clothing in Indonesia during the COVID-19 crisis but not the subjective norm and perceived behavioral control variables.
Keywords: 330; attitude; online buying intention; perceived behavioral control; religious belief; subjective norm